PENGARUH PERCEPTUAL-MOTOR TRAINING TERHADAP PERUBAHAN KEMAMPUAN KOORDINASI MATA, TANGAN, DAN KAKI ANAK TUNAGRAHITA DI SLB LANIANG MAKASSAR (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2021)
Background: Children with intellectual disabilities are children who have a lower intellectual level than normal children in their age, it causes intellectual disability children poor in childâ€™s development that effect cognitive, motoric skill, social, and emotions. Mild intellectual disabilities is the largest population of various categories of intellectual disabilities. This study aims to determine the effect of Perceptual-Motor Training on eye, hand, and foot coordination skill of intellectual disability children in SLB Laniang Makassar. Method: This study use a quasi-experimental design with the type of one group pre test and post test. The subject of this study were mild intellectual disability children in aged 10-14 years old and able to communicate. The number of respondent was 17 children and attend Perceptual-Motor Training for 12 treatment in 4 weeks. Result: The results of this study after Shapiro Wilk normality test obtained normal distribution data (p >0.05), then carried out hypothesis testing using Paired T - Test and obtained a significant value p < 0.001 (p <0.05). The data analysis from pre test and post test showed that all respondent has an increase on motor coordination. Conclusion: Perceptual-Motor Training have a significant effect to improve eye, hand, and foot coordination skill ofÂ  intellectual disabilities children in SLB Laniang MakassarKeywords: Perceptual-Motor Training, motor coordination, intellectual disabilities